Sistem Sekolah Kader Tingkat Perguruan Tinggi Muhammadiyah (Studi Komparatif Pondok Hajjah Nuriyah Shabran Dan Pendidikan Ulama Tarjih Muhammadiyah Tahun 2016) - Sahidin, Sahidin; , Dr. M. Abdul Fattah Santoso, M.Ag (2016)
The efforts of cadre forming of Muhammadiyah are conducted through three paths, they are: 1) the path of Muhammadiyah education that is through special schools of cadre such as Muallimin, Muallimat, and public Muhammadiyah schools which are alternative education, and pondok pesantren (Islamic boarding school) education which is limited, 2) the informal path in family, where the family of Muhammadiyah educate their children as future cadres of Muhammadiyah, and 3) special progran of MPK along with autonomous organizations of Muhammadiyah which last for long time according to the existence of its institution. This research aims at knowing: 1) the system of cadre schools in Pondok Shabran and PUTM in 2016 as a part of System of Muhammadiyah cadre forming, 2) the system components of cadre forming within Pondok Shabran and PUTM, 3) the similarities and the differences of system of cadre schools in Pondok Shabran dan PUTM. Viewed from the location aspect, this research is a field research. Viewed from the perspective and the level of problem discussion, this research is a descriptive research. Viewed from the type, this research is called a Comparative Study. The techniques of data collection used in this research are interview and document collection. Analysis conducted in the qualitative research is more descriptive-analytical that means that the interpretation on the content is made and arranged comprehensively and systematically. The data analysis was conducted inductively. The results of the research have revealed that: 1) Pondok Shabran and PUTM are A Functional Cadre Forming of Muhammadiyah in the part of Cadre School in the level of Muhammadiyah university that have special criteria and purposes as well as being programmed officially as the place of cadre education as conveyed on the book "Sistem Perkaderan Muhammadiyah". 2) The System Components of Cadre School of Pondok Shabran and PUTM consist of: vision, mission, and objectives, new students enrollment, educational program and curriculum, Pondok coaching, infraction and sanction, students, lecturers, facilities, and evaluation. 3) Pondok Shabran and PTUM are similar as Pondok of cadre in creating cadres of tarjih and tablig in Muhammadiyah, nevertheless, there are so many significant differences either in the concept or in the implementation. PUTM will give birth to scholars who are competent in the field of Tablig and particularly Tarjih in Muhammadiyah, as well as with Pondok Shabran which will give birth to the majority of scholars who are competent in the field of Tarjih and Tablig in Muhammadiyah and has other skills that they get in the organization and other activities outside campus. Keywords: System of Muhammadiyah Cadre Forming, Cadre School, Pondok Shabran, PUTM